PREDICTION OF ADVERSE PREGNANCY OUTCOME FOR THE FETUS ON THE BASIS OF ULTRASOUND INVESTIGATION OF THE EMBRYO AND EXTRAEMBRYONIC STRUCTURES - A. V. POMORTSEV; YU. Yu. DYACHENKO; YU. V. GRUSHEVSKAYA; V. V. LASHEVICH (Кубанский научный медицинский вестник)
Aim. Identify the most informative ultrasound criteria for the pathology of the embryo and extraembryonic structures from the 8th to the 11th weeks of gestational age in order to predict the course and outcome of pregnancy for the fetus. Materials and methods. 215 pregnant women were examined during gestation from 8 to 11 weeks. Results. By calculation of sensitivity and specificity, the most informative parameters of unfavorable development of pregnancy were revealed. Parameters of adverse course and outcome of pregnancy for the fetus are the following highly specific signs: absence of yolk sac, inadequate development of yolk sac, inadequate vascularization of the chorion. Lowspecific signs are: tone of myometrium, inadequate vascularization of the yellow body. Conclusion. Ultrasound evaluation of the embryo and extraembryonic structures during gestation from 8 to 11 weeks makes possible predicting the features of the course and the unfavorable outcome of pregnancy for the fetus.